2015
DOI: 10.1159/000381144
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Preterm Delivery by Late Cervical Length Measurement after 24 Weeks

Abstract: Objective: To examine the value of the cervical length (CL) measurement at 24-30 gestational weeks in the prediction of spontaneous preterm delivery (SPD) between 30 and 34 weeks (SPD34) and between 34 and 37 weeks (SPD37). Methods: We performed a prospective cross-sectional study. CL was measured once by transvaginal ultrasound examination between 24 and 30 weeks. Results: The study sample consisted of 1,180 low-risk singleton pregnancies. 10 women (0.85%) had a SPD34 and 60 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…The association of short CL with early delivery has mainly been studied in the second trimester but there is emerging evidence suggesting that early assessment in the first trimester may identify women at risk for PTB, albeit with lower detection rates . Additionally, in line with the original observation of Iams et al , we have lately shown that the third‐trimester CL measurement is more sensitive than the second‐trimester measurement in predicting PTB . Yet thus far, studies on third‐trimester CL use it mainly as a predictor of the time of delivery .…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…The association of short CL with early delivery has mainly been studied in the second trimester but there is emerging evidence suggesting that early assessment in the first trimester may identify women at risk for PTB, albeit with lower detection rates . Additionally, in line with the original observation of Iams et al , we have lately shown that the third‐trimester CL measurement is more sensitive than the second‐trimester measurement in predicting PTB . Yet thus far, studies on third‐trimester CL use it mainly as a predictor of the time of delivery .…”
Section: Introductionsupporting
confidence: 70%
“…Overall, first‐trimester CL seems to predict late miscarriage, second‐trimester cervical assessment performs well for very early PTB and late third‐trimester CL measurement is better for identifying late prematurity . The appropriate longitudinal chart is crucial in a sequential approach because it enables the quantification of CL change.…”
Section: Discussionmentioning
confidence: 99%
“…Iams et al compared CL measurements at 20-24 weeks with those at 28 weeks and found the latter to be superior in the prediction of PTD < 37 weeks 9 . In accordance, we examined about 1200 low-risk singleton pregnancies after 24 weeks and found that CL alone could detect about 70% of sPTD < 34 weeks with a 10% screen-positive rate 28 .…”
Section: Discussionmentioning
confidence: 97%
“…2 CL provides useful information throughout gestation but it is the mid trimester measurement that has been primarily studied. [3][4][5][6][7][8][9][10][11][12] Mid trimester CL measurement has moderate value in predicting any SPD but is quite sensitive in predicting early and very early SPD (before 32 and 28 weeks respectively) which is clinically very important. 9 The value of vaginal progesterone for preventing spontaneous preterm delivery in different high risk groups has been recognized for more than a decade.…”
Section: Introductionmentioning
confidence: 99%